Proceedings of the 2nd International Conference on Embedded Networked Sensor Systems 2004
DOI: 10.1145/1031495.1031503
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized synchronization protocols with nearest neighbor communication

Abstract: A class of synchronization protocols for dense, large-scale sensor networks is presented. The protocols build on the recent work of Hong, Cheow, and Scaglione [5,6] in which the synchronization update rules are modeled by a system of pulse-coupled oscillators. In the present work, we define a class of models that converge to a synchronized state based on the local communication topology of the sensor network only, thereby lifting the all-to-all communication requirement implicit in [5,6]. Under some rather mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(95 citation statements)
references
References 15 publications
2
93
0
Order By: Relevance
“…Whereas LISP achieves desynchronisation among nodes within a cell, DCAP achieves synchronisation between entire cells. This cell-level effect is dissimilar to existing synchronisation-based approaches [16], [17] which operate between any arbitrary nodes in fully-connected networks. DCAP utilises the sync pulse transmissions implemented by LISP to synchronise the relative phase of nodes that are to act as communication conduits between adjacent cells.…”
Section: B Part 2: Intercellular Timing Calculationmentioning
confidence: 61%
See 1 more Smart Citation
“…Whereas LISP achieves desynchronisation among nodes within a cell, DCAP achieves synchronisation between entire cells. This cell-level effect is dissimilar to existing synchronisation-based approaches [16], [17] which operate between any arbitrary nodes in fully-connected networks. DCAP utilises the sync pulse transmissions implemented by LISP to synchronise the relative phase of nodes that are to act as communication conduits between adjacent cells.…”
Section: B Part 2: Intercellular Timing Calculationmentioning
confidence: 61%
“…Lucarelli and Wang [16] define a decentralised algorithm based on synchronisation. An arbitrary partially connected graph of nodes applies a variant of the algorithm defined in [10]; it is not required that the network graph is fully connected.…”
Section: Related Workmentioning
confidence: 99%
“…Later work by Lucarelli and Wang extended this work, showing that, in theory, the modified Mirollo and Strogatz model can be applied over multi-hop topologies [103]. Researchers at Harvard University further extended this result into an actual protocol implementation for sensor networks [104].…”
Section: Firefly Oscillatorsmentioning
confidence: 94%
“…It is proved in [12] that using this mechanism, synchronization can be reached almost surely if an entity's pulse can be directly observed by all other entities. Moreover, it is shown in [13] that pulse-coupled oscillators can also synchronize if each entity communicates only with its nearest neighbors.…”
Section: Scenario and Problem Descriptionmentioning
confidence: 99%
“…3 that the curve for α = 1.35 remains well below the curve for α = 1.05. In [12,13] it is shown that the time until the sensors reach synchronization is inversely proportional to α. Intuitively, a reduced convergence time prevents the information about state class L from spreading within the whole network since the sensors within the vicinity of G resynchronize too quickly.…”
Section: Application Of Proposed Measure To Sensor Networkmentioning
confidence: 99%